Explaining Skills and Asking Skills Improve Mathematics Learning Outcomes of Elementary School Students - Frida Lusiana Yulianti; Achmad Fathoni (Universitas Pendidikan Ganesha, 2022)
Several problems developed in the field, namely, the achievement of student learning objectives, still needed to be optimal due to the need for instructors' understanding of explaining and asking skills. This study aims to analyze the relationship between explaining skills and learning outcomes in mathematics, the relationship between asking skills and learning outcomes in mathematics, and the relationship between explaining skills and questioning skills with learning outcomes in class VI MI students. This study uses a quantitative methodology and uses ex-post facto. The population of this study was 24 students, and 23 students were taken as a sample using a saturated sampling technique. Data collection tools used are surveys and documentation studies. The data collection instrument was a questionnaire with a Likert scale which had previously been evaluated for normality and reliability. Pearson product-moment correlation, multiple correlation, and F-test were used for data analysis. The results of testing the hypothesis show a significant and positive relationship between explaining skills and mathematics learning outcomes. There is a positive and significant relationship between questioning skills and mathematics learning outcomes. There is a positive relationship between explaining and asking skills and mathematics learning outcomes. It was concluded that there was a positive and statistically significant relationship between the ability to explain and the skills to ask questions with the mathematics learning outcomes of MI class VI students.